Ultrastructural study of acrosome formation in mongolian gerbil (Meriones unguiculatus) - Segatelli, T. M.; Almedia, CCD; Pinheiro, PFF; Martinez, M.; Padovani, C. R.; Martinez, F. E. (Churchill Livingstone, 2000)
Spermatogenesis is a complex and very well organized process lasting from 30 to 75 days in mammals. The spermatogenic process has been described mainly in laboratory mammals, such as the rat, while correspondent studies in wild animals are scarce. The gerbil (Meriones unguiculatus) is a small rodent native of the arid regions of Mongolia and China. Few reports are available on reproduction in the male Mongolian gerbil. The present study provides the first description of the ultrastructural alterations in spermatid cytoplasm and nucleus, with particular reference to acrosome formation in gerbils. The testes were processed by conventional transmission electron microscopy technique. Based on the development of the acrosomal system and changes in nuclear morphology, the transformation of spermatids in spermatozoon was divided into 15 steps. There were four phases in the spermiogenesis process in the gerbil: Golgi, cap, acrosomal and maturation phases. This provides the foundation for a variety of future studies of the spermiogenesis of this animal. (C) 2000 Harcourt Publishers Ltd.
Keywords: Meriones unguiculatus; spermiogenesis; testis; acrosomal system